An Unusual Case of Swimmer Puppy Syndrome in Labrador Puppy - Patel, Rajkumar; Patel, Nidhi; Gondaliya, Ravi; Sadhu, Dashrath; Raval , Sunant K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Swimmers puppy syndrome is an uncommon developmental deformity seen in neonatal puppies and kittens, in which animal's limbs,  most commonly hind limbs, are splayed laterally, and because of that animals are unable to walk or stand. This condition may also  affect the thoracic limb. It is also called flat pup syndrome, twisted legs, turtle pup, and splay leg. This condition is commonly seen in  brachycephalic breeds having short legs and a broad thoracic cavity. When trying to walk, affected animals invariably stay in sternal  recumbency and show swimmers-like movements and this movement is more commonly seen on the smooth surface. The exact cause  of this condition is unknown but many predisposing factors are responsible, viz., slippery floor, delayed neuromuscular development,  abnormal myelinization, genetic factor, weight gain exceeding skeletal muscle development, etc. This condition is commonly  seen at the 1st to 7th week of age. Currently, there is no specific and set protocol for the treatment of Swimmer Puppy Syndrome.  To our knowledge, the few case studies described therapies based on the implementation of temporary immobilizations utilizing  eight-girdle or cuff bandages and intensive physical therapy. (Karcher et al., 2018).
Keywords: Swimmer Puppy Syndrome; Labrador Puppy; animal's limbs